Self-Actualization and Trends of Narcissism in Adolescent Social Media User - Sabekti, Ria; Yusuf, Ah; Pradanie, Retnayu (Universitas Airlangga, 2019)
Introduction: Teens try to look as attractive as possible in order to gain recognition and attractiveness. Social media offers a variety of facilities so that users feel free and happy to save various experiences. The use of excessive social media triggers the emergence of cyberbulying, in the form of degrading, pressing and violent words that endanger self-esteem. Self-esteem is a factor that is related to narcissistic tendencies and one's self-actualizationMethod: The study design was cross-sectional using simple random sampling. The independent variable is the intensity of social media use. The dependent variable is the tendency of narcissism with the results of the reliability test obtained by Cronbach's Alpha 0.625, and self-actualization with the results of the reliability test obtained by Cronbach's Alpha 0.898. The research instrument used a questionnaire and was analyzed using the Kendall's test.Result: There is a relationship between the intensity of social media use and narcissistic tendencies (p = 0.005) and there is a relationship between the intensity of social media use and self-actualization (p = 0.001).Conclusion: The high intensity of social media use will affect the tendency of narcissism and self-actualization. It is necessary to supervise and improve the quality of health education to avoid excessive use of social media and optimize individual potential to achieve optimal self-actualization.